University Teachers’ Conceptions of Their Role in Teaching Problem-Solving - Natia Bendeliani; Tibor Bors Borbély-Pecze (GiLE Journal of Skills Development)
Equipping young adults with problem-solving skills is critical in today’s knowledge economy. Universities have increasingly adopted approaches like problem-based learning (PBL) to foster critical thinking and independent learning. However, while extensive research exists on the benefits of PBL, less attention has been given to studying tutors' conceptions about their role from a phenomengoraphic research perspective. This study addresses this gap by investigating university tutors' conceptions of their roles in teaching problem-solving skills within a PBL environment. Data from interviews with 15 tutors identified a progression of conceptions, from creating a safe learning environment to fostering independent learners. Each conception affects practices in tutorial groups, shaping inquiry depth, collaboration quality, and transferable skills development. The findings highlight the importance of understanding tutors’ roles in enhancing the potential of PBL to equip students with essential problem-solving skills. By uncovering the diverse ways tutors conceive their role, this research offers actionable insights for academic developers and educators aiming to refine teacher training programs and foster student-centred learning in higher education.